2005
DOI: 10.1128/iai.73.3.1744-1753.2005
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Responses toMycobacterium tuberculosisInfection in Genetically Susceptible and Resistant Mice

Abstract: The role of neutrophils in tuberculosis (TB) resistance and pathology is poorly understood. Neutrophil reactions are meant to target the offending pathogen but may lead to destruction of the host lung tissue, making the defending cells an enemy. Here, we show that mice of the I/St strain which are genetically susceptible to TB show an unusually high and prolonged neutrophil accumulation in their lungs after intratracheal infection. Compared to neutrophils from more resistant A/Sn mice, I/St neutrophils display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
219
2
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(243 citation statements)
references
References 50 publications
16
219
2
6
Order By: Relevance
“…Although the role of neutrophils in protection and pathogenesis in TB remains controversial, these effector cells clearly contribute to inflammation in acute TB [95,96]. The involvement of neutrophil-mediated lung injury could participate in the formation of necrotic and caseous granulomas [97].…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of neutrophils in protection and pathogenesis in TB remains controversial, these effector cells clearly contribute to inflammation in acute TB [95,96]. The involvement of neutrophil-mediated lung injury could participate in the formation of necrotic and caseous granulomas [97].…”
Section: Discussionmentioning
confidence: 99%
“…In the short term, the increased concentration of CXCL8 likely served to enhance neutrophil migration and surveillance of the tissues most at risk from infection. However, prolonged exposure to inflammatory cytokines can paradoxically result in deleterious effects, producing severe tissue damage, particularly in soft tissues such as the lung (Buckham-Sporer et al, 2007;Eruslanov et al, 2005;Mitchell et al, 2008) and thus increasing the susceptibility of the calves to disease. More recently, O'Loughlin et al (2011) reported that the expression of proinflammatory cytokine genes in leukocytes, including CXCL8, were upregulated up to 7 days in calves following weaning and housing.…”
Section: Variablementioning
confidence: 99%
“…Increased pulmonary neutrophilia is associated with enhanced susceptibility and exacerbated inflammatory pathology in mouse models of TB (3,39), and reduction in neutrophils correlates with TB treatment success in humans (40). Accordingly, we examined the levels of Ly6G ϩ , F4/80 Ϫ neutrophils in the lungs of RIIB Ϫ/Ϫ and wild-type C57BL/6 mice upon airborne challenge with M. tuberculosis.…”
Section: Riib ϫ/ϫ Mice Have Reduced Pulmonary Immunopathology 30 Daysmentioning
confidence: 99%
“…The enhanced level of inflammation observed in the Fc␥-chain Ϫ/Ϫ strain is not surprising because the lung bacterial burden in these mice was significantly elevated compared with that detected in wild-type mice. Because the number of neutrophils present in situ correlates well with the severity of tissue pathology in M. tuberculosis infection (38,39), studies were undertaken to enumerate this immune cell in the lungs of infected Fc␥-chain Ϫ/Ϫ mice. Not unexpectedly, quantification of neutrophil influx into the lungs revealed a significant increase in Fc␥-chain Ϫ/Ϫ mice relative to wild-type mice up to at least 15 wk after infection (Fig.…”
Section: Increased Immunopathology and Il-10 Production In Fc␥-chain mentioning
confidence: 99%